Flowering biology of Hoya lacunosa Bl. (Asclepiadaceae) in Bogor Botanical Garden - SRI RAHAYU; DWIE EKA TRISNAWATI; IBNUL QOYIM (Society for Indonesian Biodiversity, 2007)
The flowering biology of Hoya lacunose Bl. (Asclepiadaceae) has been observed in the Bogor Botanical Garden for 12 months (March 2004 - February 2005). The flower was produced continuously by the adult plant except in May and June, while the peak number of flower was on November. The flowering initiation was supposed triggered by the fluctuation to the minimum point on daily temperature (27oC to 25oC),temperature gap (8oC to 3oC), light intensity (10.6 to 2.5 MJ/m2/day), and fluctuation to the maximum point on humidity (72% to 85%) on one day followed by the normal condition afterwards. The duration of the flowering process takes 4-5 weeks, while the fruiting process takes 4-6 weeks.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Flowering Biology, Hoya lacunosa Bl. (Asclepiadaceae).